A TLR2 Agonist in German Cockroach Frass Activates MMP-9 Release and Is Protective against Allergic Inflammation in Mice - Kristen Page; John R. Ledford; Ping Zhou; Marsha Wills‐Karp (2009)
The role of TLR2 in modulating experimentally induced asthma is not fully understood. We recently identified that German cockroach (GC) frass contains a TLR2 ligand allowing us to investigate the role of a TLR2 agonist in a complex real world allergen in mediating allergic airway inflammation. GC frass exposure significantly increased airway inflammation, airway hyperresponsiveness and serum IgE levels in wild-type mice; however the same exposure in TLR2-deficient mice resulted in greatly exaggerated serum IgE and eosinophilia but diminished airway neutrophilia, suggesting a protective role for TLR2. Since GC frass inhalation usually induces airway neutrophilia, we queried the effect of neutrophil depletion on airway responses. Inhibition of neutrophil recruitment into the airways of naive wild-type mice before intratracheal inhalation of GC frass resulted in significantly increased levels of serum IgE and eosinophilia. Neutrophils are a rich source of MMP-9, and we found that MMP-9 levels were significantly increased in the airways of mice following exposure to GC frass. Importantly the levels of MMP-9 were significantly decreased in neutrophil-depleted and TLR2-deficient mice after exposure to GC frass, suggesting that TLR2 regulated MMP-9 release from neutrophils. Functionally, MMP-9-deficient mice had more acute allergic inflammation than wild-type mice, suggesting that MMP-9 was protective against experimentally induced asthma. These data suggest that TLR2 activation of neutrophils leads to release of MMP-9 which decreases allergic responses to GC frass. This suggests a protective role for TLR2 activation and MMP-9 release in the context of experimentally induced asthma in mice.